Meningkatkan Pemahaman dan Penerapan Akhlak Terpuji Melalui Metode Pembelajaran Interaktif Pada Siswa di MI Tarbiyatus Shibyan SK - Nurul Qomariyah; Nurul Hidayah; H. Nurul Huda (CV Edujavare Publishing, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping students' character, particularly in instilling noble morals. However, many students struggle to understand and apply moral values such as honesty, discipline, patience, and mutual assistance in their daily lives. This challenge arises due to a lack of student engagement in learning, monotonous teaching methods, and approaches that do not align with students' needs. This study aims to examine the effectiveness of interactive learning methods in enhancing the understanding and application of noble morals among sixth-grade elementary school students. Interactive methods, such as group discussions, simulations, educational games, and case studies, are implemented to increase student engagement and help them internalize moral values. This research employs a qualitative approach using observation, interviews, and document analysis for data collection. The findings are expected to contribute to the development of more innovative and relevant PAI learning strategies, ultimately improving students' comprehension and practice of noble morals in their daily lives.